Petalidium sebrabergense (Acanthaceae), a new species from Namibia - Swanepoel, Wessel; Wyk, Abraham E. Van (Phytotaxa, 2025)
Petalidium sebrabergense, first collected in May 2024 and easily mistaken for P. cirrhiferum, is described here as a new species. It is a range-restricted species, only known from Namibia’s Zebra Mountains, within the Kaokoveld Centre of Endemism. It typically grows on plains, hillsides, and along ephemeral riverbeds and drainage lines, primarily in soils derived from anorthosite and gabbro of the Kunene Igneous Complex. Key distinguishing features for P. sebrabergense include the pale green appearance of the plants, vegetative parts with indumentum of dense, simple, multi-cellular stalked glandular trichomes, frequently interspersed with widely spaced eglandular simple and bifurcate trichomes, often with some leaves additionally bearing sparsely branched dendritic trichomes. The flowers are borne in racemose dichasia and are notable for having the corolla lobes lilac or mauve, with both sides concolorous. A comparison of key morphological features distinguishing P. sebrabergense from P. cirrhiferum, its closest look-alike, is provided. Brief comparisons are also made with P. huillense, P. subcrispum, and P. welwitschii, species with which it can be confused, particularly in herbarium specimens. Based on IUCN Red List criteria, a provisional conservation status of Critically Endangered (CR) is recommended for the new species.